Investigation of montelukast effect on rosuvastatin induced late puberty in rats - Tamadir Hamid Wadi Aledani; Manal Nasser Al-Hayder; Suha Haitham Mohammed; Rawaa Salim Al-Mayyahi (Wolters Kluwer Medknow Publications, 2022)
Background: Puberty is a critical process for the development of sexual organs and reproductive ability. It is triggered and regulated by the hormones. Rosuvastatin can delay the onset of puberty through the inhibition of cholesterol and androgen biosynthesis. On the other hand, montelukast has protective effects against various diseases and against reproductive toxicity induced by other medications, but its effects on puberty have not been studied. Aims: Assessment of the protective effect of montelukast against rosuvastatin-induced delayed puberty. Settings and Design: At the university. Materials and Methods: Eighteen male Wistar rats aged 30 days and weighted 50-60 g were distributed to three groups (six rats per group) and intraperitoneally administered every day for 5 days with 0.2 ml of distilled water as control, 10 mg/kg of rosuvastatin and with rosuvastatin + montelukast (10 mg/kg for each drug). These animals' groups were euthanised on day 50 of age to assess the effect of rosuvastatin alone and with montelukast on the serum levels of the reproductive hormones and histological manifestations and morphometric measurements of the testes. Statistical Analysis Used: One-way analysis of variance and Bonferroni multiple tests were performed to analyse the findings using the GraphPad Prism software. Results: Treatment of rats with rosuvastatin showed a significantly decreased level of testosterone and luteinising hormone as well as histopathological and morphometric alterations in the testicular tissues in comparison with the control. Interestingly, co-treatment of rosuvastatin with montelukast could not reverse or mitigate these changes induced late puberty. Conclusion: There is no protective effect of montelukast against rosuvastatin-induced delayed puberty.